Tanggung Jawab Notaris dan Akibat yang Ditimbulkan dalam Pembuatan Perjanjian Nominee atas Kepemilikan Tanah - Esra Amanda Mora; Yunanto (Yayasan Literasi Sains Indonesia, 2026)
This study aims to comprehensively analyze the legal responsibility of notaries and the legal consequences arising from the creation of nominee agreements in land ownership involving Foreign Nationals and Indonesian Citizens. Nominee agreements are frequently used as a legal mechanism to circumvent statutory restrictions on land ownership by foreign nationals, thereby posing a serious challenge to the fundamental principles of Indonesian agrarian law. This research employs a qualitative juridical approach using a normative-descriptive research method, supported by statutory, conceptual, and case-based approaches. Data were collected through an extensive review of legal literature, analysis of court decisions, and examination of applicable positive law, particularly the Basic Agrarian Law (UUPA) and the Notary Office Act. The findings reveal that nominee agreements constitute a form of legal evasion (fraus legis) that directly contradicts the principle of nationality and the social function of land rights as stipulated in Article 21 paragraph (1) and Article 26 paragraph (2) of the UUPA. Notaries who prepare or authenticate nominee deeds may be held legally accountable under civil, criminal, and professional ethical frameworks. The legal consequences of such agreements include their classification as null and void, with the transferred land rights being reverted to state ownership. This legal enforcement mechanism is essential to safeguard Indonesia’s legal sovereignty over land, ensure legal certainty, and uphold the integrity and professionalism of notaries within the national legal system.